2021
DOI: 10.3892/mmr.2021.11939
|View full text |Cite
|
Sign up to set email alerts
|

circ‑0000212 promotes cell proliferation of colorectal cancer by sponging miR‑491 and modulating FOXP4 expression

Abstract: Colorectal cancer (CRC) is a lethal and common malignancy worldwide. Non-coding (nc)RNAs have been shown to modulate tumor progression in several types of cancer. The present study aimed to investigate the role of hsa_circ_0000212 in CRC, as a sponge of microRNA (miR)-491. The expression levels of miR-491 and forkhead box P4 (FOXP4) were analyzed using data from The Cancer Genome Atlas. The association between miR-491 and FOXP4 and the clinicopathological characteristics were also analyzed. A novel circular (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Circ‐PTPDC1 was overexpressed in GC, and deficiency of circ‐PTPDC1 inhibited GC progression 23 . In our study, hsa_circ_0043691 abundance was higher in GC tissue samples and cells, which was similar to previous research 24 . Nevertheless, lack of large sample sizes is a certain limitation in the study, which will be supplemented in future experiments.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Circ‐PTPDC1 was overexpressed in GC, and deficiency of circ‐PTPDC1 inhibited GC progression 23 . In our study, hsa_circ_0043691 abundance was higher in GC tissue samples and cells, which was similar to previous research 24 . Nevertheless, lack of large sample sizes is a certain limitation in the study, which will be supplemented in future experiments.…”
Section: Discussionsupporting
confidence: 85%
“… 23 In our study, hsa_circ_0043691 abundance was higher in GC tissue samples and cells, which was similar to previous research. 24 Nevertheless, lack of large sample sizes is a certain limitation in the study, which will be supplemented in future experiments. Thereafter, silencing of hsa_circ_0043691 distinctly repressed cell proliferation, migration, invasion, angiogenesis, and glutaminolysis metabolites, but boosted GC cell apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-1207-5p as one of the ten miRNAs expressed significantly different among gastric cancer patients with or without LNM via miRNA microarray, which could serve as a useful biomarker in the prediction of LNM [ 13 ]. MiR-491-3p, a tumor suppressor miRNA, was found decreased in many solid tissues, including brain tumor [ 14 ], colorectal cancer [ 15 ], and retinoblastoma [ 16 ]. It was worth mentioning that miR-491-3p was downregulated in gastric cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each member has a highly conserved structural domain of approximately 100 amino acids (35). Numerous studies have shown that forkhead proteins can act as transcription factors to regulate the transcription of target genes (36)(37)(38). FOXP4, a member of the P subfamily of the forkhead box (FOX) family, is a novel transcription factor (39).…”
Section: Discussionmentioning
confidence: 99%